1999
DOI: 10.1080/741943713
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity of Memory Enhancement During Interaction with a Virtual Environment

Abstract: Two experiments investigated differences between active and passive participation in a computer-generated virtual environment in terms of spatial memory, object memory, and object location memory. It was found that active participants, who controlled their movements in the virtual environment using a joystick, recalled the spatial layout of the virtual environment better than passive participants, who merely watched the active participants' progress. Conversely, there were no significant differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
102
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 12 publications
19
102
2
Order By: Relevance
“…Even though recognition time for objects was enhanced in the active condition of their study, there was no difference in accuracy between active and passive manipulation (Harman et al, 1999;James et al, 2002). Recall and recognition memory after active exploration of a virtual environment was improved for neither object identity nor location memory -instead only the spatial layout of the virtual reality environment improved (Brooks, Attree, Rose, Clifford, & Leadbetter, 1999). No prioritization of location memory was found for physically manipulated objects in a natural task, nor for relevant compared to irrelevant ones (Kirtley & Tatler, 2015).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Even though recognition time for objects was enhanced in the active condition of their study, there was no difference in accuracy between active and passive manipulation (Harman et al, 1999;James et al, 2002). Recall and recognition memory after active exploration of a virtual environment was improved for neither object identity nor location memory -instead only the spatial layout of the virtual reality environment improved (Brooks, Attree, Rose, Clifford, & Leadbetter, 1999). No prioritization of location memory was found for physically manipulated objects in a natural task, nor for relevant compared to irrelevant ones (Kirtley & Tatler, 2015).…”
Section: Introductionmentioning
confidence: 77%
“…Object recognition speed (Harman et al, 1999;James et al, 2002) and location memory Trewartha et al, 2015) increase after object manipulation. However, there is evidence that we are not necessarily better in recalling/recognizing active compared to passive objects (Brooks et al, 1999;Harman et al, 1999;James et al, 2002) and are not always left with a better spatial representation of our surroundings after active object manipulation (Kirtley & Tatler, 2015). Within a naturalistic, real-world paradigm our study investigated the role of active object handling on identity and location memory for objects.…”
Section: Discussionmentioning
confidence: 99%
“…Attree et al (1996;Brooks, Attree, Rose, Clifford, & Leadbetter, 1999) instructed participants to attend to objects while taking a route through a desktop virtual environment-specifically, to "study the objects . .…”
Section: Idiothetic Information During Walkingmentioning
confidence: 99%
“…Part of the inconsistency may be due to the use of different measures of spatial knowledge: Tests of layout recall seemed to show an attentional effect (Attree et al, 1996;Brooks et al, 1999), whereas standard tests of survey knowledge, such as pointing and distance estimates, did not (Wilson, 1999;Wilson & Péruch, 2002). However, this failure to find an effect of attention on survey tasks in desktop VR is not particularly surprising.…”
Section: Idiothetic Information During Walkingmentioning
confidence: 99%
“…Virtual learning environments have had many benefits for learners (Rose et al, 2000), however, only transfer of sub-skills has been demonstrated but overall transfer to real-world environments has not been validated (Brooks, Attree, Rose, Clifford, & Leadbetter, 1999;Cohn, Helmick, Meyers & Burns, 2000;Witmer, Bailey, & Knerr, 1996;Witmer & Sadowski, 1998).…”
Section: Future Directionsmentioning
confidence: 99%